Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,401 questions

17,804 answers

1,438 comments

43,494 users

Trigonometry help .....?

0 votes

1. If tan A = n tan B , sin A = m sin B, prove that cos ^ 2 A = (m ^ 2 - 1) / (n ^ 2 - 1)
2. If cos ^ 2 a - sin ^ 2 a = tan ^ 2 b, prove that tan ^ 2 a = cos ^ 2 b - sin ^ 2 b
3. If cosec a - sin a = m and sec a - cos a = n, prove that [ { (m ^ 2) * n} ^ 2/3 ] + [ { m * ( n ^ 2 ) } ^ 2/3 ] = 1

asked Jan 29, 2013 in TRIGONOMETRY by andrew Scholar

2 Answers

0 votes

Tan A = n Tan B

Divide each side by ' Tan B '

n = Tan A / Tan B

Quotient Identities is TanA = sinA/cosA

n = [sinA/cosA] / [sinB/cosB]

Then n = sinAcosB / cosAsinB

And sinA = m sinB

Divide each side by ' sin B '

m = sinA / sinB

Now take  (m2-1) / (n2-1)

= [(sinA / sinB)2 -1] / [(sinAcosB / cosAsinB)2-1]

 Rewrite the expression with common denominator.

= [(sin2A - sin2B) / sin2B] / [(sin2Acos2B - cos2Asin2B) / (cos2Asin2B)]

Simplify (sin2A - sin2B)(cos2Asin2B) / (sin2B)(sin2Acos2B - cos2Asin2B)

Pythagorean Identities: sin2θ = 1 - cos2θ

= [(1 - cos2A) - (1 - cos2B)]cos2A(1 - cos2B) / (1 - cos2B)[(1 - cos2A)( cos2B) - cos2A(1 - cos2B)

= [ - cos2A  + cos2B)]cos2A(1 - cos2B) / (1 - cos2B)[(cos2B - cos2A cos2B - cos2A + cos2Acos2B

=  (cos2B - cos2A)cos2A(1 - cos2B) / (1 - cos2B) [cos2B - cos2A]

= cos2A (cos2B - cos2A)(1 - cos2B) / (1 - cos2B) [cos2B - cos2A]

= cos2A

There fore

(m2 - 1) / (n2 - 1) = cos2A

answered Jan 29, 2013 by richardson Scholar
0 votes

cosec a-sin a = m and sec a-cos a = n,

Recall reciprocal identities is coses A = 1/sinA and secA = 1/cosA

cosec a - sin a = m

(1/sin a) - sin a = m

Rewrite the expression with common denominator.

(1 - sin2 a)/sin a = m

Pythagorean Identities is 1 - sin2 θ = cos2θ

cos2a/sin a = m

m = cos2a/sin a

And sec a-cos a = n

Similarly n = sin2a/cos a

Now take [{m2×n}2/3] + [{m×(n2)}2/3]

m2×n  = [cos2a/sin a]2×[sin2a/cos a]

= (cos4a)(sin2a)/(sin2a)(cos a)

Simplify m2×n = cos3a

{m2×n}2/3 = (cos3a)2/3 = cos2a

m×n2 = (cos2a/sin a)×(sin2a/cos a)2

= (cos2a)(sin4a)/(sin a)(cos2a)

Simplify m×n2=sin3a

{m×n2}2/3 = {sin3a}2/3 = sin2a

[{ m2×n}2/3 + { m×n2}2/3] = cos2a + sin2a

So, [{ m2×n}2/3 + { m×n2}2/3] = cos2a + sin2a = 1

There fore [{ m2×n}2/3 + { m×n2}2/3] = 1

answered Jan 29, 2013 by richardson Scholar

Related questions

asked Jul 24, 2014 in TRIGONOMETRY by anonymous
asked Jul 11, 2014 in TRIGONOMETRY by anonymous
asked May 17, 2014 in TRIGONOMETRY by anonymous
asked May 13, 2014 in TRIGONOMETRY by anonymous
asked Dec 21, 2014 in TRIGONOMETRY by anonymous
...